Gambaran fungsi kognitif penderita parkinson di Poliklinik Saraf RSUP Prof. Dr. R. D. Kandou Manado - Tarukbua, Febrilya F.; Tumewah, Rizal; PS, Junita Maja (Universitas Sam Ratulangi, 2016)
Abstract: Parkinson's disease (PD) is a neurodegenerative disease that can cause cognitive function impairment. This study aimed to obtain the cognitive function in Parkinson’s patients at the Neurology Clinic Prof. Dr. R. D. Kandou Hospital Manado. This was a descriptive prospective study by using MMSE and MoCA Ina instrument. There were 31 patients of Parkinson’s disease during November and December 2015. Of the 31 patients, 27 had cognitive function impairment. The highest percentages among them with cognitive function impairmentwere male gender, age group 60-71 years, high school education or of the same level. and had no job including retired male patients.Keywords: Parkinson’s disease, cognitive function Abstrak: Penyakit Parkinson ialah penyakit neurodegeneratif yang dapat disertai penurunan fungsi kognitif. Penelitian ini bertujuan untuk mendapatkan gambaran fungsi kongnitif pada pasien Parkinson di Poliklinik Saraf RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ini deskriptif prospektif dengan menggunakan instrumen penelitian MMSE dan MoCA Ina. Hasil penelitian mendapatkan 31 pasien Parkinson selang bulan November-Desember 2015. Terdapat 27 pasien dengan penurunan fungsi kognitif, terbanyak dijumpai pada jenis kelamin laki-laki, kelompok usia 61-70 tahun, tingkat pendidikan SMA/sederajat, dan yang sudah tidak bekerja termasuk laki-laki pensiunan. Kata kunci: penyakit Parkinson, fungsi kognitif